وبائيات قمل الرأس لدى تلاميذ الحلقة الأولى في مدارس محافظة اللاذقية - بدور, رولا (Latakia University Journal -Medical Sciences Series, 2019)
يهدف البحث لإجراء دراسة إحصائية وبائية عن معدل انتشار قمل الرأس في المدارس الابتدائية في محافظة اللاذقية ودراسة مدى ارتباط هذه الإصابة بعوامل مختلفة وذلك في محاولة لتحديد أهم العوامل المؤهبة في محاولة للحد من انتشار هذه الإصابة حيث تم إجراء المسح على /23/ مدرسة ابتدائية موزعة في أنحاء مختلفة من محافظة اللاذقية, وذلك بالتعاون مع مديرية الصحة المدرسية في المحافظة, وتم إجراء فحص سريري لكافة طلاب هذه المرحلة ومن ثم تم ملء استمارات تفصيلية خاصة بالطلاب المصابين تنوعت نسبة الحدوث بين المدارس أما ارتباط الإصابة بالعمر فلم يكن هاماً في حين أن الارتباط كان قوياً بين الإصابة والإصابة العائلية المرافقة وكذلك الأمر بين الإصابة والسوابق العائلية والشخصية كما وجد تناسب طردي بين الإصابة والحالة الاقتصادية للأهل .كما وجد نفس التناسب الطردي بين الإصابة والحالة الثقافية للأهل. This piece of research aims to conduct an epidemiological statistical study of the prevalence of pediculosis capitis at the elementary schools in Lattakia. It also studies the correlation of pediculosis capitis with different factors in order to define the most important precipitating factor to prevent the prevalence of this infection. This study has investigated 23 elementary schools in different locations in Lattakia, in cooperation with Lattakia Department of Schooling Health. However, clinical examination of all students was performed, then detailed questionnaires were made for the infected students. The prevalence of P.C among different schools varied. The relation of the disease with student’s ages was unimportant, while the correlation between the infection and the accompanied family infection was serious; the same for the infection, the family and patient history, as well a correlation was found between the infection and the family economy status. The same correlation was found between the infection and parent’s education.